Peradaban Teks: Konsep Penafsiran Al-Quran Syed Nuqaib Al-Attas Menghadapi Modernisasi - D.I. Ansusa Putra; Zikwan Zikwan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Civilization of the Text: The Concept of Al-Quran Interpretation by Syed Naquib Al-Attas in Facing ModernizationSyed Nuqaib al-Attas projected a civilization rooted in the Quran and Hadith texts which were motivated by the massive secularization of values in Muslim countries by offering the concept of al-Quran interpretation. This paper aims to compile the concept of al-Attas Quranic interpretation, which is still scattered in some of his works, by building the structure of ideas and worldviews of the concept that the author calls metalinguistic interpretation. This paper uses an interpretive discourse analysis method. This method constructs the discourse by al-Attas ideas in his works, especially on two themes: 1) Islamic civilization and 2) the interpretation of the Quran. This article concludes that al-Attas offers cross-disciplinary knowledge that integrates the text of the Quran with other perspectives, namely: philosophy, intellectual tasawwuf, linguistics, and metaphysics. These cross-disciplines will produce an authoritative reading of the Quranic text and serve as a foundation to build a civilization facing modernity with various terminological offers, such as Ta'dib, din, ikhtiyar, and Islam. Furthermore, this position makes al-Attas different from several other figures such as Nasr Hamid Abu Zayd and Jamaluddin al-Afghani in the same discourse